2020
DOI: 10.1016/j.drugpo.2019.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Changes in alcohol and cigarette consumption in response to medical and recreational cannabis legalization: Evidence from U.S. state tax receipt data

Abstract: Background: Whether medical or recreational cannabis legalization impacts alcohol or cigarette consumption is a key question as cannabis policy evolves, given the adverse health effects of these substances. Relatively little research has examined this question. The objective of this study was to examine whether medical or recreational cannabis legalization was associated with any change in state-level per capita alcohol or cigarette consumption.Methods: Dependent variables included per capita consumption of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
(51 reference statements)
2
23
0
Order By: Relevance
“…Despite the relationship between cannabis and cigarette use, the increased negative consequences associated with co‐use and the increasing use and acceptance of cannabis alongside increasing cannabis legalization, little is known about how cannabis legalization might impact upon the co‐use of cigarettes and cannabis versus the use of cigarettes without cannabis or cannabis without cigarettes. One US national study reported a higher prevalence of cigarette–cannabis co‐use in states with versus without MCL in 2013 (5.8 versus 4.8%, P < 0.01) [46], whereas another study [47] found that per capita cigarette sales did not differ overall for states with versus without MCL or RCL. Similarly, several studies showed no RCL‐related changes in cigarette use [48,49] or cannabis use [50] among young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relationship between cannabis and cigarette use, the increased negative consequences associated with co‐use and the increasing use and acceptance of cannabis alongside increasing cannabis legalization, little is known about how cannabis legalization might impact upon the co‐use of cigarettes and cannabis versus the use of cigarettes without cannabis or cannabis without cigarettes. One US national study reported a higher prevalence of cigarette–cannabis co‐use in states with versus without MCL in 2013 (5.8 versus 4.8%, P < 0.01) [46], whereas another study [47] found that per capita cigarette sales did not differ overall for states with versus without MCL or RCL. Similarly, several studies showed no RCL‐related changes in cigarette use [48,49] or cannabis use [50] among young adults.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies included in this review focused on population aggregated sales data, either in terms of total aggregated sales of alcoholic beverages per capita 68 or in terms of Nielsen scanner data sales. 27 The findings from these two studies suggested that alcohol sales were lower in states that adopted MMLs.…”
Section: Resultsmentioning
confidence: 99%
“…However, the findings in the study by Veligati et al, which also included additional alcohol policy measures that better captured the overall alcohol environment and covered a much longer time period, suggested that this association was not statistically significant. 68 Moreover, Veligati et al suggested that states that further adopted adult-use cannabis policies subsequently had an increase in per capita alcohol sales; 68 Baggio et al did not consider these subsequent changes. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of other substance use and its association with the loosening of state-level restrictions on cannabis, the evidence is also mixed (for review see, e.g., Darnell, 2020;Guttmannova et al, 2016;Risso et al, 2020;Smart & Pacula, 2019). Most recently, Veligati et al (2020) demonstrated that neither alcohol nor cigarette consumption (as measured by state tax receipt data) has increased or decreased as a result of "recreational" and medical cannabis legalization. Evidence regarding substitution versus complementarity in the association between cannabis and other substances likely remains mixed because these populationlevel studies do not allow examination of whether intraindividual change over time in use of one substance is associated with intraindividual change in use of another (for a brief review of design and dataset recommendations, see, e.g., Guttmannova et al, 2016Guttmannova et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%